A Systematic Review of Vestibular Evoked Myogenic Potential in Individuals with Motion Sickness - Furtal, Silvestina Winston; Thomas, Amith; Yerraguntla, Krishna (Annals of Otology and Neurotology, 2022)
The otolith of vestibular system in the human body helps in maintaining the static balance. Travelling can cause defect in static balance that may lead to motion sickness. The evidence showing the relation between vestibular evoked myogenic potential (VEMP) that assesses otolith function and motion sickness is contrasting. The current systematic review is aimed to understand outcomes of published articles in reporting association between vestibular evoked myogenic in individuals with motion sickness. For this study, the database used is PubMed, Scopus, ProQuest, CINHAL, and Web of Science. The data is extracted from the final articles where VEMP is done on individuals with and without motion sickness. The total articles included are 125 out of which five articles used for the systematic review. In this study, motion sickness susceptibility questionnaire is used to assess individuals with and without motion sickness. The latency and amplitude of both cervical VEMP (cVEMP) and ocular (oVEMP) of individuals with and without motion sickness are normal. However, the review indicates a significant change in the interaural asymmetry ratio of both cVEMP and oVEMP results in individuals with motion sickness. This shows that there might be a variation in the functional asymmetry in the otoliths. From the review, it is clear that there might be otolith changes due to motion sickness that can have a smaller impact on the interaural asymmetry ratio in VEMP. These findings can be further applied for the diagnostic purpose in individuals with motion sickness.
Keywords: cervical vestibular evoked myogenic potentials; motion sickness; ocular vestibular evoked myogenic potentials; otolith organ